Color Protection from UV irradiation of artificial dyes with grape seed (Vitis vinifera) extract - Sonja L Knowles; Wei Sheng; Stephanie Davis; Vincent P Sica; Christopher J Pulliam; Timothy R Baker; Lijuan Li; Jennifer M Marsh; Rui Fang; Guillermo F Padilla-González; Monique SJ Simmonds (Journal of Photochemistry and Photobiology, 2022)
Hair color fade is an important issue for consumers who use permanent hair colorants and is caused by both washing and UV exposure. The mechanism of light-induced fading was explored using a solution model system and shows that both UV and visible light contribute to color fade and a significant amount of fade is via radical pathways. It was demonstrated that this fade can be reduced by incorporation into a conditioner of a Grape Seed Extract (GSE) that has antioxidant activity. The efficacy of performance was linked to phytochemistry of the extract, specifically catechins and procyanidins and illustrated the importance of extract choice. Levels of these phytochemicals varied between different samples of GSE tested and this correlated well with measured antioxidant performance as measured by ORAC and FRAP. Light-induced fading of hair treated with a permanent hair color was measured with a selection of the GSE extracts. Benefits in protection were measured as a reduction in color lightness changes vs the starting hair color before light exposure.